2018
DOI: 10.1002/ase.1828
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional Visualization Software Assists Learning in Students with Diverse Spatial Intelligence in Medical Education

Abstract: This study evaluated effect of mental rotation (MR) training on learning outcomes and explored effectiveness of teaching via three-dimensional (3D) software among medical students with diverse spatial intelligence. Data from n = 67 student volunteers were included. A preliminary test was conducted to obtain baseline level of MR competency and was utilized to assign participants to two experimental conditions, i.e., trained group (n = 25) and untrained group (n = 42). Data on the effectiveness of training were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
0
11
0
6
Order By: Relevance
“…Haciendo referencia al uso de las TIC en el contexto educativo, la Realidad Virtual ha tenido gran transcendencia en los últimos años ya que se ha demostrado cómo esta metodología influye en la motivación de los estudiantes favoreciendo el proceso de enseñanza y aprendizaje, tal y como señalan Marín y Muñoz (2018), Jamil et al (2019), Cagiltay, Ozcelik, Berker y Menekse (2019), Jacobsen et al (2019).…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation
“…Haciendo referencia al uso de las TIC en el contexto educativo, la Realidad Virtual ha tenido gran transcendencia en los últimos años ya que se ha demostrado cómo esta metodología influye en la motivación de los estudiantes favoreciendo el proceso de enseñanza y aprendizaje, tal y como señalan Marín y Muñoz (2018), Jamil et al (2019), Cagiltay, Ozcelik, Berker y Menekse (2019), Jacobsen et al (2019).…”
Section: Discusión Y Conclusionesunclassified
“…Actualmente, el uso de la Realidad Virtual en el campo pedagógico se encuentra en auge (Dos Santos & Dos Santos, 2019;Sural, 2018), dado que se está incluyendo en distintos planes de estudios (Huttar & Brintzenhofeszoc, 2019), siendo considerado como un recurso pedagógico efectivo que apoya el aprendizaje de los estudiantes (Jamil et al, 2019), además de innovador (Slater et al, 2019). La Realidad Aumentada es accesible, por diversos medios, entre ellos el teléfono móvil (Degli et al, 2019), lo que la hace ser personalizable, accesible e interactiva (Nijman et al, 2019).…”
Section: Introductionunclassified
“…Similarly in this study, while the increase in the scores for men in the second exam after receiving the training was statistically significant (p=0.008), the increase in the score between the two exams was not found to be statistically significant for women (p=0.879). Jamil et al [18] found that the scores of men were higher than women in both tests, and a significant increase was identified in the scores of both women and men. Although this study's objective was not to evaluate the difference between genders, it can be stated based on the obtained data that a statistically significant difference is present between the scores obtained in the two tests by male students.…”
Section: Discussionmentioning
confidence: 95%
“…According to a study by Jamil et al, 97% of students found the use of 3D modeling software in education more effective as compared to plastic models. [18] The use of 3D modeling in medical education will ensure greater visualization of dynamic processes in the mind, and allow for more effective use in both diagnosis and treatment in future. [21] Anatomy quiz Mean±SD p The low number of participants can be considered as a limiting factor of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to remote availability, there are countless viewing options, use is nondestructive in nature, and a digital cadaver is not opposed by religious beliefs (Estai and Bunt, 2016). There is some evidence that digital cadaver use improves student performance by improving student spatial abilities (Guimarães et al, 2019), improving factual and spatial knowledge acquisition (Yammine and Violato, 2015), and increasing user satisfaction (Darras et al, 2019; Jamil et al, 2019; Triepels et al, 2020). Digital cadavers are credited with increased learning when the user exerts control over the experience rather than observation alone (Jang et al, 2017).…”
Section: Life Cycle Analysismentioning
confidence: 99%